MENDETEKSI OBJEK DUA DIMENSI DENGAN MENGGUNAKAN MATLAB MENDETEKSI OBJEK DUA DIMENSI DENGAN MENGGUNAKAN MATLAB MENDETEKSI OBJEK DUA DIMENSI DENGAN MENGGUNAKAN MATLAB (Information Technology and Telematics, 2013)
Image processing is very useful to improve the quality of the image, eliminatingOne area that is related to image processing pattern recognition on a two-dimensional object. Objective: This study was conducted to produce a system that can identify and recognize an object or a simple pattern, like squares, pentagons, circles and right triangles, based on shape and size. Methods: The method used in the identification of this object is, statistical pattern recognition. Results: The application program is developed capable of detecting simple objects are computerized. Conclusion: Every object has a two-dimensional object that is not upright, so that the analysis using matlab necessary rotation to the right or to the left. This is done manually, image processing can be done by using mathematical equations, In Matlab programming language has some hidden tools that can be used in image processing and digital signal processing.Keywords: detection, two-dimensional wake